Tinjauan Hukum Islam tentang Perlindungan Saksi dalam Undang-undang Perlindungan Saksi dan Korban Tahun 2006 - Muhammad Shafwan; M. Zayin Chudlori (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2019)
This article aims to find out: (1) how is witness protection in Law of the Republic of Indonesia Number 13 of 2006 and witness protection in Islamic law? The results of the study concluded that; firstly, the protection of a witness in the Law of the Republic of Indonesia Number 13 of 2006 (Article 5) explains that a witness has the right to obtain protection for his personal, family, and property security, and is free from threats relating to testimony which will, is, or has given. The meaning of protection here is the efforts to fulfill the rights and provide assistance in the sense of security to witnesses that must be carried out by LPSK (Witness and Victim Protection Agency) or other institutions per the provisions of this law. Secondly, even though the mechanism for protecting a witness is not regulated in detail, but Islam highly appreciates a witness who is willing to give testimony in the disclosure of a case, namely by forbidding killing the witness.